SYNTHESIS OF SILVER NANOPARTICLES FROM SILVER NITRATE SOLUTION USING GREEN TEA EXTRACT (CAMELIA SINENSIS) AS BIOREDUCTOR (Universitas Negeri Semarang, 2017)
The synthesis of silver nanoparticles with micro size is highly required in antibacterial fields. The biorefinery material is highly potential as a bioreductor which is applied in the synthesis of nanoparticles. The bioreductor is made from green tea leaves extraction using aquadest to extract its active substance, the catechin which is derived from polyphenol. The polyphenol can reduce the synthesis of silver nanoparticles naturally. The result of FTIR analysis from green tea leaves extract containing polyphenol shown in the uptake functional groups is -OH group located in 3425 cm-1, C=O group located in 1635 cm-1, C=C group located in 1527, and 1442 cm-1 , and C-O group located in 1234 cm-1. The precursors of AgNO3 was used as the main synthetic material. The synthetic condition was resulted from the reaction between the extraction of green tea extract and AgNO3 as the precursors in the variation of synthetizing time. The heating process during synthesizing is done in 50 ˚C along with stirring to foster the creation of silver nanoparticles. The analysis result of XRD shows that silver nanoparticles has the diffraction peaks in the angle of 2 theta that are 44.08, 64.40, and 77.51. The types of silver nanoparticles is Ag0 nanoparticles with face-centered cubic crystal structure. Based on TEM analysis, the size and particle size distribution can be determined using image J. The distribution shows that the longer synthesizing time, the bigger nanoparticles produced. With synthesizing times at 24 hours, 6 hours, 3 hours, and 2 hours produce average particle size of 26.4 nm; 9.2 nm; 8.4 nm; and 7.4 nm respectively.